Generations towards COVID-19 Pandemic - Agnieszka Ewa Barczykowska; Katarzyna Pawełek (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: Generation affiliation is an important variable, differentiating perception and taking behaviour strategies in difficult situation of the pandemic. Research Aim: The aim of the article is to present the characteristics of modern generations and the differences between them in terms of experiencing/ the COVID-19 pandemic. Evidence-based Facts: The review and critical analysis of Polish and English literature of the subject, available reports and reportswas used as a method. Based on scientific literature and studies, the characteristics of modern generations were presented: Builders, Baby Boomers, Generation X, Millennials (Generations Y and Z), Alpha. The focus was on their chosen specific characteristics. The intergenerational differences in life experiencing and the consequences of the COVID-19 pandemic are shown. Summary: The analyses indicate that each generation, to varying degrees, has faced the problem of coping with losses in three areas: behavioral and biological, psychosocial and material. Conclusion: Covid-19 pandemic did not leave any of the presented generations without its influence. Apart from shared experiences and consequences, each generations has its own problems. There problems being identified is key to introduce assistance actions and overcoming of pandemic's negative aftermath.